Legal abortion in childhood: the official discourse and the reality of a Brazilian case - Lucimara Fabiana Fornari; Emiko Yoshikawa Egry; Mariana Sbeghen Menegatti; Karen Namie Sakata So; Rosa Maria Godoy Serpa da Fonseca; Maria Amélia de Campos Oliveira (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to identify the ideological perspectives of official discourses in relation to sexual violence, childhood pregnancy and access to legal abortion based on a Brazilian case. Methods: a qualitative documentary study. Data collection was carried out in documents published on official Brazilian websites, between August and December 2020. The analytical categories of gender and generation supported data analysis. Results: a total of 39 documents were selected and three empirical categories were identified: Protection against violence in the legislation and the (re)production of injuries in reality; Facing sexual violence against children by the Brazilian State; Being a Brazilian girl: gender and generational oppressions. Final considerations: the ideological perspectives of official discourses in relation to the case showed a lack of compliance with advances in Brazilian legislation on issues related to child violence and adult-centric authoritarianism, with the imposition of gender and generation subalternity.